Participatory varietal selection in fodder oats under temperate conditions of Kashmir valley - Mehraj, Uzma; Ahmad, Mushtaq; Abidi, Ishfaq; Zaffar, Gul; Shikari, Asif B. (The Indian Journal of Genetics and Plant Breeding, 2016)
A study was done on the participatory varietal selection (PVS) for adoption of improved forage oat varieties in Kashmir under Himalayan conditions. The study assessed how this approach influence farmers’ uptake of the introduced forage oat varieties and determined socioeconomic, bio-physical and institutional factors that influence the adoption of these improved forage oat varieties. Therefore a survey was carried out in Shopian, Pulwama, Srinagar, Bandipora and Gandarbal districts in Kashmir. Data were collected from 113 farmers using a predesigned questionnaire. Before administering the individual questionnaire, a participatory rural appraisal (PRA) was conducted by selecting 50 households from 16 selected sites. The sites were selected from central, north and south areas of Kashmir valley. Three sites from Districts of Srinagar, four sites from Gandarbal, four from Shopian and five sites selected from Pulwama to identify background information, production constraints as well as the farmers perception about varietal specification of fodder oats. Descriptive statistics were generated using χχ χχ χ2-test. The most preferred genotypes identified by the farmers through PVS were SKO-90, SKO-96 and SKO-98. These genotypes needs to be evaluated further by Baby Trial evaluation system on big plot size and over many more locations to corroborate the real performance and finally to recommend the varieties for up scaling through Participatory Seed Production under such ecologies.